Advanced Ti‐Doped Fe2O3@PEDOT Core/Shell Anode for High‐Energy Asymmetric Supercapacitors. Issue 12 (14th April 2015) - Zeng, Yinxiang; Han, Yi; Zhao, Yitong; Zeng, Yan; Yu, Minghao; Liu, Yongjiang; Tang, Haolin; Tong, Yexiang; Lu, Xihong
<x xml:space="preserve">Abstract</x> An effective strategy to significantly boost the capacitive properties of Fe2O3‐based anodes by Ti doping and poly(3, 4‐ethylenedioxythiophene) (PEDOT) coating is successfully demonstrated. The Ti‐Fe2O3@PEDOT electrode exhibits a significant capacitance improvement and exceptionally cyclic stability. A remarkable energy density of 0.89 mWh cm−3 can be obtained for a high‐performance asymmetric supercapacitor device consisting of Ti‐Fe2O3@PEDOT and a MnO2 anode.